Early stridor onset and stridor treatment predict survival in 136 patients with MSA. (27th September 2016) - Giannini, Giulia; Calandra-Buonaura, Giovanna; Mastrolilli, Francesca; Righini, Matteo; Bacchi-Reggiani, Maria Letizia; Cecere, Annagrazia; Barletta, Giorgio; Guaraldi, Pietro; Provini, Federica; Cortelli, Pietro
Abstract : Objective: To evaluate the predictive value of stridor and its latency of onset and to investigate the role of stridor treatment in a cohort of patients with multiple system atrophy (MSA) referred to a tertiary center. Methods: We retrospectively identified patients diagnosed with MSA referred to our department beginning in 1991 and evaluated at least yearly during the disease course. Stridor was defined as present when confirmed by a whole night video-polysomnography and as early if presenting within 3 years of disease onset. Survival data, from disease onset to time of death, were calculated with Kaplan-Meier curves. Predictors were identified in univariate and multivariable Cox regression analyses. Results: We included 136 patients with MSA; 113 were deceased at the time of study. Stridor was diagnosed in 42 patients, and 22 presented early stridor onset. Twelve of the 31 patients treated for stridor received tracheostomy, and 19 received continuous positive airway pressure. Overall survival did not differ between patients with and without stridor, while patients with early stridor onset had a worse prognosis than those developing this symptom later. In the stridor subgroup, early stridor onset was an unfavorable survival predictor. Stridor treatment was significantly associated with survival in our population. The Kaplan-Meier curve did not reveal significant differences in survival between the 2 treatments even though there was a trend toward longer disease duration in patients receiving tracheostomy. Conclusions: Our results demonstrated that early stridor onset is an independent predictor for shorter survival and that tracheostomy could control stridor, influencing disease duration.